Hygiene Sanitasi Terhadap Kejadian Wasting Pada Bayi Usia 0-59 Bulan: Hygiene And Sanitation On Wasting Incidence In Infants Aged 0-59 Months - Triveni; Rici Gusti Maulani; Nuari Andolina (Pro Health Jurnal Ilmiah Kesehatan, 2023)
Wasting is a state of acute malnutrition that is common in areas with low socio-economic status which can be caused by inadequate nutritional intake and the presence of disease. Wasting is part of malnutrition, one of the classifications of nutritional status indicators for BB/TB. Children who are said to be thin are those who have a low weight that is not suitable for their height. The purpose of this study was to obtain a description, analysis, and interpretation of environmental hygiene and sanitation factors on wasting in toddlers (0-59 months) in Pasaman and Bukittinggi City. This research is an analytic survey research with a case-control design. The research was conducted at the Tanah Datar District Health Center, in May-June. The total population is 8442. The quantitative sample is 216 people using a proportionate stratified sampling technique. Data collection was carried out using a questionnaire, tracing, and reviewing reports or documents related to the problem under study. Analysis of chi-square test data and multivariate binary logistics. The statistical test results show that there is a significant relationship between wasting and hygiene and sanitation (0.005, OR 3.169). The results of the research on the influence of hygiene and sanitation on wasting incidents suggest that health officials should be more promotive and preventive about the importance of information about hygiene and sanitation and maintaining environmental sanitation for reducing cases of wasting under five in Tanah Datar District.  Keywords: hygiene, sanitation, wasting, nutritional problems ABSTRAK               Wasting adalah suatu keadaan kekurangan gizi akut yang banyak terdapat di daerah dengan sosial-ekonomi rendah yang dapat disebabkan oleh asupan nutrisi yang inadekuat dan adanya penyakit Wasting merupakan bagian dari kekurangan gizi, salah satu klasifikasi dari indikator status gizi BB/TB. Anak yang dikatakan kurus adalah mereka yang memiliki berat badan rendah yang tidak sesuai terhadap tinggi badan yang dimilikinya. Tujuan penelitian ini adalah untuk mendapatkan deskripsi, analisis dan interprestasi factor hygiene dan sanitasi lingkungan terhadap kejadian wasting pada balita (0-59 bulan) di KabupatenPasamandan Kota Bukittinggi. Penelitian ini adalah penelitian survey analitik dengan desain case control. Penelitian dilakukan dipuskesmas Kabupaten Tanah Datar, bulan Mei-Juni. Jumlah populasi 8442. Sampel kuantitatif 216 orang dengan menggunakan teknik proportionate stratified sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner, menelusuri dan menelaah laporan atau dokumen yang berhubungan dengan masalah yang diteliti. Analisis data uji chi-square dan multivariate binary logistic. Hasil uji statistic menunjukkan bahwa ada hubungan yang signifikan anatara kejadian wasting dengan Hygiene dan Sanitasi (0.005, OR 3.169). Hasil penelitian pengaruh hygiene dan sanitasi dengan kejadian wasting sehingga disarankan untuk dinas kesehatan lebih menggiatkan promotif dan preventif tentang pentingnya informasi tentang hygiene dan sanitasi dan menjaga sanitas lingkungan bagi penurunan kasus wasting balita di Kabupaten Tanah Datar. Kata kunci: hygiene, sanitasi, wasting, masalah gizi